Blockchain-enabled power distribution side management: model and method. (July 2020) - Yang, Jianlin; Fei, Fei; Wang, Haiqun; Guo, Mingxing; Lü, Ran; Jia, Kevin
Abstract: With the development of the "ubiquitous power internet of things", the shortcomings of the traditional centralized power trading mechanism in power distribution side have gradually become apparent, e.g., low flexibility in power usage. And blockchain technology gains some insight to deal with these problems due to its distributed nature. To this end, the paper implements a blockchain-based multi-channel energy management model on the Hyperledger Fabric blockchain platform to carry out a transaction-driven power management method in the power distribution side. Simulation results show its operability and effectiveness.